People managing forests: the links between human well-being and sustainability - Colfer, C.J.P.; Byron, Y. (Resources for the Future and Center for International Forestry Research, 2001)
This book examines aspects of human well being (identified in earlier research on sustainable forest management) in a variety of contexts. The 26 authors reports results of research conducted in six countries (Indonesia, Brazil, Cameroon, Gabon, Trinidad, and the United States), in conjunction with a series of social science methods tests designed to assess human well being in areas where logging was taking place. These social science results were obtained as part of a project on criteria and indicators for sustainable forest management. This book, comprised of 16 chapters, includes sections focusing on gender and diversity, and a conservation ethic, as well as two principles found important for sustainable forest management: security of intergenerational access to resources, and rights and responsibilities to manage co-operatively and equitably. It includes a chapter looking at geographical and temporal comparisons related to human well being and sustainability.